Ekonomi Sirkular Ummat Meningkatkan Kesejahteraan Civitas Akademika Dengan Adanya Bisnis Berbasis Al-Maqasid Al-Syariah - Nur Fitri Hidayanti (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
Cleanliness is part of faith. This study aims to find out how far the waste management process in the Muhammadiyah Mataram University Campus is, knowing that so far the waste on the Muhammadiyah Mataram University Campus has not been handled as well as possible. It can be seen that there are still many landfills that are not handled properly and waste is simply dumped on the side of the river which is next to the University of Muhammadiyah Mataram Campus.This study uses a qualitativ approach and observations were made from August 2021 to December 2021. The research findings are is a waste bank that is focused and committed to the development of solid waste trading in NTB, with the concept of “Together we turn waste into rupiah, turn problems into blessings”. This concept is a derivation from the implementation of a waste business scale-up that is in line with the objectives of the Shari'a (al-maqasid al-syariah). The scale up of the waste bank management business is carried out in several stages. First, minimizing the environmental impact caused by measuring the quantity of waste that can be managed and has economic value. Aspects of competence, quality, ethical morals, trustworthiness, in the process of the waste business trade system, as an effort of hifzu dien (maintaining religion), and hifzu al-nasb (keeping offspring). Second, knowledge, understanding and awareness of waste management as a resource, as an effort of hifzu al-nafs (protecting the soul), hifzualaql (protecting the mind). Third, increasing the number of unit waste banks that are fostered, building a wider network, through education, strengthening the customer's economy as an effort to protect property.